2014
DOI: 10.14260/jemds/1805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Incidence of Malignancy in Multinodular Goiter

Abstract: Multinodular goiters are more often looked upon as potentially benign type. But the incidence of malignancy in MNG is on the rise. The objective of this study was to determine the incidence of malignancy in multinodular goiter. In this prospective study total 40 patient of thyroid swellings (MNG, STN & diffuse goitre) were seen in the M.K.C.G. Medical College Hospital, Southern Orissa, during August 2011-July 2013. Thyroid hormone profile and FNAC was done in all cases while, USG was done in 28 cases and all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…In present study, the overall incidence of all malignant cases was observed as 12.6% on the basis of histopathological diagnosis. These findings are consistent with many national and international findings 25,26 but in contrast to the study of Beigh et al, which reported 72.34% of all the malignant cases of thyroid 27 . Papillary carcinoma of thyroid was reported as common malignant tumor of thyroid with 67.5% in current study.…”
Section: Discussionsupporting
confidence: 92%
“…In present study, the overall incidence of all malignant cases was observed as 12.6% on the basis of histopathological diagnosis. These findings are consistent with many national and international findings 25,26 but in contrast to the study of Beigh et al, which reported 72.34% of all the malignant cases of thyroid 27 . Papillary carcinoma of thyroid was reported as common malignant tumor of thyroid with 67.5% in current study.…”
Section: Discussionsupporting
confidence: 92%